Three-Dimensional Evaluation on Ecotypic Diversity of Traditional Chinese Medicine: A Case Study of Artemisia annua L. - Li, Lin; Josef, Brinckmann A.; Liu, Bing; Zheng, Sihao; Huang, Linfang; Chen, Shilin (Frontiers in Plant Science, 2017)
Artemisinin is the first-line drug for anti-malaria recommended by the World Health Organization (WHO). As the sole natural plant source of artemisinin, ecotypes of Artemisia annua L. vary widely in artemisinin content between nations, and China is the main producing area of A. annua. Here we present a three-dimensional evaluation on ecotypic diversity of A. annua from 12 main producing areas in China using high-performance liquid chromatography coupled with evaporative light scattering detection (HPLC ELSD) method, DNA barcoding and ecological analyses. The results indicated that A. annua exhibited high ecotypic diversity. A. annua grown in the South of the Qinling Mountains-Huaihe River Line had a high artemisinin content, whereas the northern ones were low. Similar pattern was noted in the genetic diversity. The southern A. annua had high intraspecific variation in contrast to the northern A. annua. In terms of ecological analyses, humidity and sunshine time could be the major limiting ecological factors that affect the accumulation of artemisinin. This is the first reported three-dimensional evaluation integrating chemical, molecular and ecological analyses of the ecotypic diversity of A. annua. The work will facilitate exploring the genetic basis of chemical variations and developing strategies for the breeding and cultivation of high quality A. annua.